To determine whether each equation describes the line that passes through the points (4, 6) and (6, 2), we can first find the slope of the line defined by these two points.
The slope \( m \) is given by: \[ m = \frac{y_2 - y_1}{x_2 - x_1} = \frac{2 - 6}{6 - 4} = \frac{-4}{2} = -2 \]
Now that we know the slope is -2, we can use the point-slope form of the equation of a line, which is: \[ y - y_1 = m(x - x_1) \]
Using the point (4, 6): \[ y - 6 = -2(x - 4) \quad \text{(This matches the first equation)} \]
Now using the point (6, 2): \[ y - 2 = -2(x - 6) \quad \text{(This matches the second equation)} \]
Let's analyze the other given equations:
-
\( y - 2 = -2(x + 6) \)
- Substitute \( x = 6 \): \[ y - 2 = -2(6 + 6) = -2(12) = -24 \quad \Rightarrow \quad y = -22 \quad (\text{Not on the line}) \]
- Answer: No
-
\( y - 2 = -2(x - 6) \)
- Substitute \( x = 6 \): \[ y - 2 = -2(6 - 6) = -2(0) = 0 \quad \Rightarrow \quad y = 2 \quad (\text{Is on the line}) \]
- Answer: Yes
Now we can summarize the answers:
- \( y−6=−2(x−4) \) Yes
- \( y−4=−2(x−6) \) Yes
- \( y−2=−2(x+6) \) No
- \( y−2=−2(x−6) \) Yes
So the final answers are:
- Yes
- Yes
- No
- Yes